2018
DOI: 10.1080/14767058.2018.1442429
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal outcomes of placenta increta and percreta from a multicenter study in China

Abstract: The incidence of placenta increta and placenta percreta is likely to increase in China. The depth of placenta implantation is associated with the severity of outcomes. Placenta percreta tends to have worse maternal and neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 13 publications
3
19
0
1
Order By: Relevance
“…The hysterectomy rate of penetrating placenta accreta was 50%, which was higher than the hysterectomy rate of placenta increta and placental accreta, which were 15.8%% and 0% respectively. Some scholars revealed that the depth of placenta implantation was associated with the severity of outcomes; A large-scale retrospective analysis in China found that the hysterectomy rate for penetrating placenta accreta was 43.3%, and the hysterectomy rate for placental accreta was 11.2%, which were statistically signi cant and similar to our research [23]. Another study also showed the rate of hysterectomy during cesareans and the total hysterectomy rate were signi cantly higher in the percreta than the accreta group (52.9% vs 20.9%, 84.3%vs 23.8%).…”
Section: Discussionsupporting
confidence: 88%
“…The hysterectomy rate of penetrating placenta accreta was 50%, which was higher than the hysterectomy rate of placenta increta and placental accreta, which were 15.8%% and 0% respectively. Some scholars revealed that the depth of placenta implantation was associated with the severity of outcomes; A large-scale retrospective analysis in China found that the hysterectomy rate for penetrating placenta accreta was 43.3%, and the hysterectomy rate for placental accreta was 11.2%, which were statistically signi cant and similar to our research [23]. Another study also showed the rate of hysterectomy during cesareans and the total hysterectomy rate were signi cantly higher in the percreta than the accreta group (52.9% vs 20.9%, 84.3%vs 23.8%).…”
Section: Discussionsupporting
confidence: 88%
“…The present results revealed that risk factors for PA were pre-pregnancy weight, gravida, number of miscarriages, number of CS, history of PROM, previous transverse incisions with cesarean section, a history of PP, and with prenatal hemorrhage or placenta previa. These results are consistent with previous studies [7][8][9][10][11][12][13][14].…”
Section: Risk Factors For Placenta Accretasupporting
confidence: 94%
“…Placenta accreta is one of the most common complications in obstetrics, and it was reported that [11] its incidence had increased annually from 1.593% in 2011 to 6.176% in 2015. In addition, a previous study showed that the prevalence of PA between 1982 and 2018 ranged from 0.01 to 1.1% [19].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most case series include only one or two placenta percreta series—the condition associated with the highest risk of maternal and fetal morbidity and mortality. In clinical practice, the exact MAP classification criteria still vary from study to study, especially in terms of placenta accrete [ 3 ]. Although histological examination is recommended, it may not be accurate when the uterus is conserved.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a previous history of cesarean section is associated with a high risk of MAP. The increasing MAP prevalence and severity of the related adverse outcomes have attracted high levels of attention, especially in cases with placenta increta and percreta [ 3 ]. In this study, we sought to focus on placenta increta and percreta.…”
Section: Introductionmentioning
confidence: 99%